(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2019)
We develop a combinatorial method for computing and reducing of the possibilities of distance distributions of ternary orthogonal array (TOA) of given parameters (n, M, τ). Using relations between distance distributions of arrays under consideration and their relatives we prove certain constraints on the distance distributions of TOAs. This allows us to collect rules for removing distance distributions as infeasible. The main result is nonexistence of (17,108,34) TOA. Our approach allows substantial reduction of the number of feasible distance distributions for known arrays. This could be helpful for other investigations over the classification of the ternary orthogonal arrays.